Very early onset inflammatory bowel disease (VEO-IBD); spectrum of clinical presentation, diagnostic tools and outcome in children - Huma Arshad Cheema; Nadia Waheed; Anjum Saeed; Zafar Fayyaz; Muhammad Nadeem Anjum; Muhammad Arshad Alvi; Syeda Sara Batool (Journal of the Pakistan Medical Association, 2021)
Background: Very early-onset inflammatory bowel disease (VEO-IBD) is defined as diagnosis of Ulcerative Colitis (UC) or Crohn’s Disease (CD) in children under six years of age. Genome wide association studies have linked a strong genetic component responsible for VEO-IBD. Approximately, 30-40% children of VEO-IBD have underlying immunodeficiency states. We aimed to study the spectrum of presentation, underlying monogenetic defects and outcome in VEO-IBD. Methods: This is a prospective, observational study conducted at division of Gastroenterology, the Children’s Hospital & the Institute of Child Health, Lahore, over 2 years. Children developing features of IBD under six-years of age were included. Data included demography, clinical presentation, diagnostic tools and outcome. Gastroscopy and colonoscopy were performed in all patients in addition to basic work up done for associatedimmunodeficiency states and molecular genetics. SPSS version 21 was used for analysis. Continuous...